Pengembangan Wilayah Berbasis Subsektor Pertanian Hortikultura di Kecamatan Plaosan Kabupaten Magetan - Sigit Dwi Kuncoro (Department of Urban and Regional Planning, Diponegoro University, 2014)
Plaosan distric is one of the Magetan regency where its economic activities supported by agricultural activities. The leading agricultural sector is horticulture. But there are problems that indicate the agricultural sector is not maximized in the improvement of the local economy in the Plaosan district. BPS note’s shown the District Plaosan among 18 (eighteen) districts in Magetan has the number of poor people (pre-prosperous) the second largest after the Panekan District, and there is an increasing trend of poor people from 2008 till 2011 with an average of 1.5% per year. This study aims to determine the regional development of agriculture-based on horticultural subsector in Plaosan district using quantitative descriptive with three analysis. First, analysis of the characteristics and potential of the area. Second, the analysis of the factors driving and inhibiting. Third, analysis of the effect of horticultural farming activities for improving the welfare of farmers and their contribution in the development of the region in Plaosan district. The results of this study are as follows: First, the availability of agricultural land, labor, still very potential to be developed. Second, agricultural activities have not yet had significant impact on the welfare of farmers which shown by indicators of Farmers Exchange / NTP average in Plaosan district is 100.96. This figure is far from the average exchange rate of the national horticultural farmers agricultural sector that is equal to 109.34. Third, the most influential factor affecting the results of the exchange rate of farmers is the availability of local materials and equipment, which still have not been fulfilled. Horticulture sector in the Plaosan district can be developed as the driving force of the economic society as well as being the leading sectors that encourage development in the Plaosan. Therefore, we need an effort to increase the exchange rate of farmers and horticulture performance optimization through: (1) improvement of upstream agricultural sub-sector, in this case related to the provision of seeds, fertilizers, and drugs. (2) Improvement of support subsector associated to generating activities and providing necessary services such as marketing, irrigation, transportation, research development, extension and consultancy.